KELAYAKAN TEKNO-EKONOMI PLTSA INSINERASI 10 MW DI TPA TERJUN KOTA MEDAN - siahaan , Daniel Afrizal; Prabowo, Eri (Integrative Perspectives of Social and Science Journal, 2026)
Medan City faces increasing waste generation that has pressured the carrying capacity of the Terjun landfill and created the need for a more sustainable treatment option. This study analyses the techno-economic feasibility of a 10 MW waste-to-energy incineration plant at the terjun landfill by comparing moving-grate, fluidized-bed, and rotary-kiln technologies. A quantitative secondary-data approach was used to asses waste generation , waste composition, energy potential, and financial indicators including NPV, IRR, benefit-cost ratio, payback period, and sensitivity analysis. The result show that medan has sufficient waste supply to support plan operation. Moving-grate provides the highest annual power output and feasible financial performance, while rotary-klin record the highest NPV under less realistic city-scale CAPEX assumptions. Revenue is the most sensitive variable. overall, moving-grate is the most realistic option for the terjun landfill context